If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4a + -5) = (2a + -3) Reorder the terms: (-5 + 4a) = (2a + -3) Remove parenthesis around (-5 + 4a) -5 + 4a = (2a + -3) Reorder the terms: -5 + 4a = (-3 + 2a) Remove parenthesis around (-3 + 2a) -5 + 4a = -3 + 2a Solving -5 + 4a = -3 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -5 + 4a + -2a = -3 + 2a + -2a Combine like terms: 4a + -2a = 2a -5 + 2a = -3 + 2a + -2a Combine like terms: 2a + -2a = 0 -5 + 2a = -3 + 0 -5 + 2a = -3 Add '5' to each side of the equation. -5 + 5 + 2a = -3 + 5 Combine like terms: -5 + 5 = 0 0 + 2a = -3 + 5 2a = -3 + 5 Combine like terms: -3 + 5 = 2 2a = 2 Divide each side by '2'. a = 1 Simplifying a = 1
| -9x-4=7x-16 | | y+5=0.2y+4.4 | | x+6-340+64=570 | | 10n=18n | | X+x^2-58=128 | | 8(2)-2x=46 | | 0.9x-2.9=0.7 | | 5(-w-2z)-6(-7z+5w)= | | 2x-5=+7 | | 22.3-3u=3.1 | | 42x-13x-30x=46 | | 8x=4x+44 | | (5k-25)-(6k+2)+7= | | -7x-4=-6x-8 | | 0.50t+3=1 | | 5y+5z=15 | | 5x+2=7+4x | | 6+4x=6x-8x-2 | | -4w-6(4x-4w)+3x= | | 3a+b-20=a-4b+42 | | 5(7x+2)-3=35x+7 | | -.5x+4=-2 | | 7w-(-z+6w)+5z= | | 150+(4n)=10n | | 4y-6+y+37=5y+40-3y | | 3x+6x-6x-2x+2=23 | | x+20=90-x | | 3x^2+18x=(-30) | | 3x^2+18x=-30 | | 1+3n=-7-5n | | 266-w=107 | | -4(-2w-3x)-2(-x-7w)= |